Breast MRI in ductal carcinoma in situ (DCIS) of the breast in clinical practice - Turtiainen, Saara; Rinta-Kiikka, Irina; Koskivuo, Ilkka (SAGE Publications, 2026)
Background and Aims:
Ductal carcinoma in situ (DCIS) is a non-invasive form of breast cancer with increasing incidence in recent decades. Early detection and accurate staging of DCIS are crucial for determining the appropriate treatment approach, with breast-conserving surgery (BCS) being the standard when feasible. The role of preoperative magnetic resonance imaging (MRI) in DCIS remains controversial, particularly in relation to its potential to identify incidental findings that may influence surgical decisions. This study aims to evaluate the clinical value of preoperative MRI in patients with pure DCIS, focusing on its impact on surgical management and the potential influence of incidental findings on mastectomy rates.
Material and Methods:
A retrospective review of 91 patients with pure DCIS who underwent preoperative MRI between 2014 and 2019 at Tampere University Hospital, Finland. Patients were divided into two groups: “No incidental MRI findings” and “Incidental MRI findings” with the latter leading to further imaging and biopsies. Surgical approaches and the time delay between diagnosis and surgery were compared. Tumor sizes estimated by MRI, mammography, ultrasound, and histopathology were assessed for correlation.
Results:
Incidental MRI findings were identified in 22% of patients, with a higher mastectomy rate in “Incidental MRI findings” (65.0%) group compared to the “No incidental MRI findings” (41%) group. Despite the higher mastectomy rate in the “Incidental MRI findings” group, most incidental findings were benign. The evaluated mean tumor size was largest on MRI (48 mm) compared to mammography (32 mm) and ultrasound (27 mm). MRI was found to overestimate tumor size, unlike mammography and ultrasound. No significant difference in the delay between MRI and surgery was observed between the two groups.
Conclusions:
In DCIS, incidental findings on MRI were associated with higher mastectomy rate, but overtreatment or unnecessary mastectomies were not detected. MRI may assist surgical decision-making in patients with pure DCIS.